The influence of the Earth’s magnetic field on strapdown inertial gravimetry using Q-Flex accelerometers: static and dynamic experiments - Johann, Felix; Becker, David; Becker, Matthias; Hoss, Matthias; Löwer, Alexander; Förste, Christoph (Journal of Geodesy, 2021)
In recent strapdown airborne and shipborne gravimetry campaigns with servo accelerometers of the widely used Q-Flex type, results have been impaired by heading-dependent measurement errors. This paper shows that the effect is, in all likelihood, caused by the sensitivity of the Q-Flex type sensor to the Earth’s magnetic field. In order to assess the influence of magnetic fields on the utilised strapdown IMU of the type iMAR iNAV-RQH-1003, the IMU has been exposed to various magnetic fields of known directions and intensities in a 3-D Helmholtz coil. Based on the results, a calibration function for the vertical accelerometer is developed. At the example of five shipborne and airborne campaigns, it is outlined that under specific circumstances the precision of the gravimetry results can be strongly improved using the magnetic calibration approach: The non-adjusted RMSE at repeated lines decreased from 1.19 to 0.26 mGal at a shipborne campaign at Lake Müritz, Germany. To the knowledge of the authors, a significant influence of the Earth’s magnetic field on strapdown inertial gravimetry is demonstrated for the first time.